2013
DOI: 10.1371/journal.pone.0080573
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Lifetime Traumatic Events and Subsequent Chronic Physical Conditions: A Cross-National, Cross-Sectional Study

Abstract: BackgroundAssociations between lifetime traumatic event (LTE) exposures and subsequent physical ill-health are well established but it has remained unclear whether these are explained by PTSD or other mental disorders. This study examined this question and investigated whether associations varied by type and number of LTEs, across physical condition outcomes, or across countries.MethodsCross-sectional, face-to-face household surveys of adults (18+) were conducted in 14 countries (n = 38, 051). The Composite In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 61 publications
4
123
0
Order By: Relevance
“…These groups were similar in age (39.20 14.54 years for paper, 36.32 12.17 years for internet, P = 0.188) and disease activity P-HBI [median (IQR): 4 (2-8) and 5 (3)(4)(5)(6)(7)(8)(9), respectively, P = 0.058]. In the final cohort, the mean age was 38.38 years, the majority of patients were women, and over half were married or living with a partner (Table 1).…”
Section: Demographics and Clinical Datamentioning
confidence: 93%
See 1 more Smart Citation
“…These groups were similar in age (39.20 14.54 years for paper, 36.32 12.17 years for internet, P = 0.188) and disease activity P-HBI [median (IQR): 4 (2-8) and 5 (3)(4)(5)(6)(7)(8)(9), respectively, P = 0.058]. In the final cohort, the mean age was 38.38 years, the majority of patients were women, and over half were married or living with a partner (Table 1).…”
Section: Demographics and Clinical Datamentioning
confidence: 93%
“…These experiences impact on physical and mental health [2,3]. In a large study of various populations and controlling for mental illness, it has been shown that stressful life events have a significant relationship with a variety of physical illnesses [4]. Although there is no evidence that stress is a primary cause of IBD, several studies have shown that patients with IBD experience increased stress and threatening life experiences before disease exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…19 In fact, the assessment of environmental stressful events has been used in several household national surveys to validate predictors of mental health disorders such as posttraumatic stress, depression, and anxiety disorders, as well as addictive disorders. 32,33 In this study, we also validated the LTE-Q using the latent class analysis method, allowing the estimation of the latent construct adversity with binge drinking and cocaine use. (4) Brazilian validation of the LTE-Q…”
Section: Discussionmentioning
confidence: 99%
“…At least 1 prior study found a dose-response association between the number of separate traumatic events and self-reported chronic conditions that was independent of PTSD and other mental disorders. 17 Additional research is needed to determine whether these results would extend to objective CVD outcomes in women.…”
Section: Circulationmentioning
confidence: 99%